Executing Public Notary Officials Role In Making Cooperative Agreement - Fani Pratama; Akhmad Khisni (Jurnal Akta, 2018)
True cooperative is a business entity that stands based on family rules, in Indonesia cooperative stand up and walk before the independence of Indonesia. First it was a banking company in Purwokerto, Central Java founded by Raden Aria Wiria Atmadja aided and forwarded by a Resident De Wolf Van Westerorde using cooperative system is not running because it is considered more pro natives. Trip the cooperative development of the pre and post-independence Indonesia severely affected the economy of Indonesia. Development side by side with other economic system, cooperatives perceived need of the legality of the law in all of their business activities. The legality of a cooperative is the agreement of establishment of cooperatives. A public official who has the authority to make the authentic act is a notary.Keywords: Cooperative, Agreements, Notary.